Prediksi Produksi Bawang Merah di Kota Yogyakarta menggunakan Metode Fuzzy Mamdani - Zaky Noer Jati; Tri Hastono; Ferdi Andrian (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses the prediction of shallot production in Yogyakarta City using the Fuzzy Mamdani method. The research is important due to the impact of shallot production fluctuations on the national economy. The Fuzzy Mamdani method was chosen for its high level of flexibility and tolerance for existing data. Data was collected from Bappeda DIY and shallot farmers to build the prediction model. The prediction implementation was carried out using Matlab R2015a with Fuzzy Logic Matlab Toolbox. The prediction results were evaluated using the RMSE value. The study concludes that the Fuzzy Mamdani method can be used for predicting shallot production with an error rate of 14.11%. However, the study suggests a review of the data used in the prediction to ensure its accuracy. Several references used in the study are also included.